2014
DOI: 10.2340/00015555-1772
|View full text |Cite
|
Sign up to set email alerts
|

Hair Zinc Levels and the Efficacy of Oral Zinc Supplementation in Patients with Atopic Dermatitis

Abstract: Zinc deficiency in patients with atopic dermatitis (AD) and the use of zinc supplementation is still controversial. We measured hair zinc levels in 58 children with AD and 43 controls (age range 2-14 years). We also investigated the efficacy of oral zinc supplementation in AD patients with low hair zinc levels by comparing eczema assessment severity index (EASI), transepidermal water loss (TEWL), and visual analogue scales for pruritus and sleep disturbance in patients receiving zinc supplementation (Group A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 33 publications
3
56
0
10
Order By: Relevance
“…It seems that normalized zinc levels lead to balance inversion between cell-mediated (Th1) and humoral (Th2) immunity in favor of the Th1 response. Furthermore, a recent study investigating the efficiency of oral zinc supplementation in AD demonstrated favorable effects on AD supporting the abovementioned study results [20]. …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It seems that normalized zinc levels lead to balance inversion between cell-mediated (Th1) and humoral (Th2) immunity in favor of the Th1 response. Furthermore, a recent study investigating the efficiency of oral zinc supplementation in AD demonstrated favorable effects on AD supporting the abovementioned study results [20]. …”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that increased oxidative stress (OxS) plays a role in the pathophysiology of childhood AD and the use of an antioxidant agent might be a useful strategy for the treatment of AD [19]. A low zinc level could cause the membrane barriers’ problem and this problem could increase transepidermal water loss (TEWL), which makes the skin dry clinically, and the penetration of allergens could be easier [20]. This can affect the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a key pathophysiological role in diseases such as diabetes, cardiovascular diseases, and cancer [16]. Zn deficiency is observed in patients with inflammatory diseases such as atopic dermatitis [17], asthma [18], and Crohn's disease [19]. Zn supplement can decrease oxidative stress in isolated mononuclear cells and can also decrease the expression of genes encoding inflammatory cytokines which are known to generate reactive oxygen species (ROS) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have hypothesized that AD is associated with a non-specific decrease concerning trace metals34. Furthermore, we previously reported that zinc (Zn) supplementation led to clinical improvement in AD patients with low hair Zn levels5. However, there is little data on other hair mineral levels in AD.…”
mentioning
confidence: 99%